The impact of reclamation activities towards fishermen socio-economics at Merambong Shoal, Gelang Patah, Johor - Jumain, Nora Azura; Kamarulzaman, Nitty Hirawaty (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
This paper presents the impact of reclamation activities towards fishermen socio-economics at Merambong Shoal, Gelang Patah, Johor. Merambong Shoal lies on the Malaysian side of the border that cuts through the Straits of Johor. There are four jetties that are situated on the shores facing the Merambong Shoal and locals usually use these jetties to land their daily catch. According to the Development of Fisheries (DOF) Malaysia, there are approximately around 300 fishermen at Gelang Patah and only 100 of them were actively fishing at Merambong Shoal. A few years back, Merambong Shoal was well known that has abundant seagrass bed. Seagrass bed is a vital part of the marine ecosystem due to their productivity level, habitat and nursery areas for numerous vertebrate and invertebrate species. However, with recent reclamation activities at the area have provided negative impacts to the number of fish catches, and thus have worsen the socio-economics status of the fishermen.